Pengembangan Modul Ajar Dengan Pendekatan Kontekstual Untuk Meningkatkan Numerasi Siswa Kelas VIII SMP - Zega, Mira Astuti; Mendrofa, Ratna Natalia; Lase, Sadiana; Mendrofa, Netti Kariani (Jurnal PEKA (Pendidikan Matematika), 2026)
ABSTRACT: The low numeracy skills of students and the limited use of contextual learning materials at UPTD SMP Negeri 1 Gunungsitoli Utara formed the basis for conducting this research. These conditions indicate the need to develop learning materials that can help teachers implement meaningful learning experiences for students. This study aims to develop and evaluate the feasibility of a contextual teaching module to enhance students’ numeracy skills. The research employed a Research and Development (R&D) design using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included expert validators, teachers, and eighth-grade students. The instruments used were expert validation questionnaires, teacher and student response questionnaires, and numeracy achievement tests. The collected data consisted of qualitative data in the form of expert feedback and quantitative data from questionnaires and test results. The findings show that the developed contextual teaching module achieved a high level of feasibility, with a validation score of 92.01%, positive responses from teachers (95%) and students (86.9%), and an 81.72% improvement in students’ numeracy skills. Therefore, the developed contextual teaching module is considered feasible for use as an instructional tool to support the enhancement of students’ numeracy skills at the junior high school level.  ABSTRAK: Rendahnya kemampuan numerasi siswa dan terbatasnya penggunaan perangkat pembelajaran kontekstual di UPTD SMP Negeri 1 Gunungsitoli Utara menjadi dasar dilakukannya penelitian ini. Kondisi tersebut menunjukkan perlunya pengembangan perangkat pembelajaran yang dapat membantu guru mengimplementasikan pembelajaran yang bermakna bagi siswa. Penelitian ini bertujuan untuk mengembangkan dan menguji kelayakan modul ajar kontekstual dalam meningkatkan kemampuan numerasi siswa. Jenis penelitian yang digunakan adalah research and development (R&D) dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Subjek penelitian terdiri atas validator ahli, guru, dan siswa kelas VIII. Instrumen yang digunakan meliputi angket validasi, angket respons guru dan siswa, serta tes hasil belajar numerasi. Data penelitian mencakup data kualitatif berupa saran dari ahli dan data kuantitatif berupa hasil angket dan tes. Hasil pengembangan menunjukkan bahwa modul ajar kontekstual memiliki tingkat kelayakan tinggi berdasarkan hasil validasi sebesar 92,01%, memperoleh respons positif dari guru (95%) dan siswa (86,9%), serta mampu meningkatkan kemampuan numerasi siswa dengan persentase peningkatan 81,72%. Dengan demikian, modul ajar kontekstual yang dikembangkan dinyatakan layak digunakan sebagai perangkat pembelajaran yang mendukung peningkatan kemampuan numerasi siswa di tingkat SMP.